Co-developing an intervention to facilitate safe and early transition to neonatal home care for very preterm infants: a mixed-method study evaluating the impact of patient and public involvement - Arwehed, Sofia; Thernström Blomqvist, Ylva; Carlsson Filipowicz, Elin; Axelin, Anna (BioMed Central Ltd, 2026)
Background:
Very preterm born infants face elevated risks of adverse neurodevelopmental outcomes, with prolonged hospitalisation associated with poorer cognitive, motor, and language development. Contributing factors include limited parental presence, insufficient stimulation, and exposure to stressful procedures. In Nordic countries, neonatal home care programmes support early discharge by enabling parents to manage nasogastric tube feeding at home under specialist supervision. However, inconsistent discharge practices delay the transition to home by creating parental uncertainty and making the process more vulnerable to staff discontinuity. This study aimed to co-develop an intervention to support safe and early discharge and evaluate the impact of engaging parents and healthcare professionals as collaborators throughout the research process.
Methods:
A descriptive mixed-methods study with an embedded process evaluation was conducted guided by participatory action research methodology. A Steering Committee consisting of two parents, a neonatal nurse, a researcher, and a coordinator managed the process. Five parents and seven healthcare professionals from three Swedish neonatal units representing diverse care models were purposively recruited for creative workshops, ensuring diversity in gender, culture, and professional background. Patient and public involvement (PPI) was evaluated through anonymised impact log surveys, a process log, standardised meeting minutes, semi-structured interviews with Steering Committee members, and a written survey of public contributors. Field notes, post-it notes, mind maps, and audio recordings supported data validation.
Results:
The co-development process resulted in an intervention tool designed to visualise the neonatal care journey, discharge criteria, infant development, and parental preparation, including milestones to track progress and strengthen parental roles. More than 90% of stakeholder recommendations were implemented, closely aligning the tool with family needs. Key enablers of meaningful collaboration were a respectful, emotionally safe environment and a shared commitment to collaborative decision-making. Paired reflection supported individual expression. Parents appreciated the opportunity for emotional processing, while professionals valued gaining deeper insight into family perspectives.
Conclusion:
This study demonstrates the feasibility and value of PPI in developing a neonatal care intervention. The resulting tool is intended to enhance predictability, standardisation, and timely discharge preparation while strengthening the parental role. A forthcoming feasibility study will assess its potential to improve discharge practices, support parental well-being, and facilitate safe and early transition to home.